Rumination, Mood Issues and Quality of Life among Young Adults - Shafqat Sahfique; Alishba Malik (Pakistan Journal of Positive Psychology, 2026)
The present study aims to find the connection among rumination, mood issues, and quality of life among young adults. Rumination is a maladaptive pattern of repetitive negative thinking that has been consistently associated with emotional difficulties and impaired psychological functioning. During young adulthood, individuals experience numerous developmental, academic, occupational, and interpersonal challenges that may increase their vulnerability to mood-related problems and negatively affect their quality of life. The study concludes that rumination is an important cognitive vulnerability factor influencing emotional well-being and overall quality of life among young adults. These findings highlight the need for early psychological screening and interventions targeting maladaptive rumination to reduce mood-related problems and improve quality of life. Therefore, the present study aimed to investigate the relationship between rumination, mood issues, and quality of life among young adults. A quantitative correlational research design was employed. A total sample size was consisted on (N=300) young adults aged 18–30 years were recruited using a convenience sampling technique from public and private universities in Pakistan.